The Implementation of Behavioral Rehearsal Towards Activity of Daily Living Skill Enhancement of People with Intellectual Disability - Justin Foera-era Lase; Lina Favourita; Rini Hartini RA (Indonesian Journal of Social Work, 2017)
Intellectual Disability Issues are family dependency in performing Activity of Daily Living (ADL). This research aims to know and examine the implementation of behavioral rehearsal to improve the ability of ADL to take care of AH, AJ, JS intellectual disability. The method used in this research is the method of action research with post-positivism social work research paradigm. Data collection techniques used were in-depth interviews, observation and documentation studies. Data source used is primary data source and secondary data source. The behavioral rehearsal application is carried out in accordance with the principle of action research that is participatory based on the stages of action research, therapy procedure, and involving the family in each stage of the activity. The results showed that the implementation of rehearsal behavioral increase the ability of ADL to take care of self AH, AJ, and JS. This shows an increase in the behavior of AH, AJ, JS in wearing clothes, wearing pants and wearing shoes. Additional stage of information in rehearsal behavioral is not relevant to intellectual disability. The practical implications of the results of this research indicated that the rehearsal behavioral application of intellectual disability should pay attention to three things: family involvement, repetition, and providing detailed and systematic instruction.